2020
DOI: 10.1177/0954406220973061
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of Von Karman swirling bioconvective nanofluid transport from a rotating disk in a porous medium with Stefan blowing and anisotropic slip effects

Abstract: In recent years, significant progress has been made in modern micro- and nanotechnologies for micro/nano-electronic devices. These technologies are increasingly utilizing sophisticated fluid media to enhance performance. Among the new trends is the simultaneous adoption of nanofluids and biological micro-organisms. Motivated by bio-nanofluid rotating disk oxygenators in medical engineering, in the current work, a mathematical model is developed for steady convective von-Karman swirling flow from an impermeable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 64 publications
(113 reference statements)
3
27
0
Order By: Relevance
“…As a result, nanofluids are a handy and efficient solution to filling this gap, as well as good for increased heat transmission. There are several benefits for employing nanofluids in solar energy, for instance [ 10 , 11 , 12 ]: Nanofluids have remarkable optical characteristics, demonstrating a strong absorption and la ow remittance in both the solar and infrared spectra. Nanofluids have a greater stability rate and an excellent absorption medium across a broad range of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, nanofluids are a handy and efficient solution to filling this gap, as well as good for increased heat transmission. There are several benefits for employing nanofluids in solar energy, for instance [ 10 , 11 , 12 ]: Nanofluids have remarkable optical characteristics, demonstrating a strong absorption and la ow remittance in both the solar and infrared spectra. Nanofluids have a greater stability rate and an excellent absorption medium across a broad range of temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The system of Equations ( 4)-( 9) is converted to ordinary differential equations with the help of the below mentioned similarity transformation. [48][49][50]…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The fluid speed with mixed convection parameters grew quicker but delayed the magnetic field parameter and the Rayleigh number bioconvection. Some important studies on the bioconvection mechanism can be found from the list of references [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%